The novel immuno-regulatory effects of the Hepatitis C Virus (HCV) protein p7 - CONVERY, ORLA MAEVE (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2018)
Hepatitis C virus (HCV) is a significant global pathogen and a leading cause of liver disease. HCV is highly effective at establishing a chronic infection, however its acute infection is often asymptomatic, for reasons that remain undefined. It is HCV?s ability to successfully modulate immune responses and create a host environment that enhances viral survival, that has led us to hypothesise a specific role for HCV proteins in limiting pathology and allowing the virus to remain clinically silent in many patients. One strategy used by HCV to modulate innate immunity, is the upregulation of a key suppressor of cytokine signalling (SOCS) protein, SOCS3; a powerful inhibitor of cytokine signalling. HCV infection induces SOCS3 expression in both immune cells and hepatocytes, suggesting that it is an important component in HCV?s arsenal of weapons that target anti-viral immunity. We hypothesised that individual HCV proteins could induce SOCS3 and that their identification and mechanistic elucidation might pave the way for future novel anti-inflammatory therapeutics. We found that the HCV proteins, Core, E2, p7 and NS2, all induced SOCS3 protein expression. Focusing on p7, we found that its immune-regulatory induction of SOCS3 was linked to its ion channel activity. We then sought to determine the intracellular signalling pathways responsible for SOCS3 induction, and carried out oPPOSUM web-based bioinformatic analysis to identify potential transcriptional targets. We found putative transcription factor binding sites for STAT3, STAT1, AP-1 and ELK1, directing us towards both the JAK/STAT and MAPK pathways, as regulators of p7-induced SOCS3. We found that p7 enhanced STAT3 phosphorylation and subsequent GAS promoter activity, while shRNA knockdown of STAT3 abrogated p7-mediated SOCS3 induction, strongly suggesting that STAT3 was required for p7-induced SOCS3 expression. Interestingly, while STAT1 is well known as a regulator of SOCS3, p7 expression had no effect on its activation, but as predicted by oPPOSUM, ERK was phosphorylated in the presence of p7. In fact, a significant increase in both AP-1 and ELK1 promoter activity indicated that MAPK signalling was involved in p7?s immuno-modulatory activity. In agreement with our hypothesis, inhibition of ERK activation prevented p7-mediated SOCS3 upregulation, revealing its importance in SOCS3 induction. Having observed that p7?s ion channel activity and p7-induced STAT3 and ERK pathways regulated SOCS3, we wondered what this immuno-modulatory process achieved for the virus. Since our lab had previously found that the HCV polyprotein reduced TNF signalling via SOCS3, we wondered if p7 induction of SOCS3 could individually suppress not only TNF, but also other key cytokine responses, such as proinflammatory IL-1 signalling and anti-viral IFN-mediated STAT1 activity. We found that p7 significantly inhibited IL-1-mediated NF-kappaB promoter activity, however to our surprise, overexpression of p7 did not affect IFN-induced pSTAT1 or ISRE transcriptional activity. We discovered that p7 significantly inhibited TNF-mediated NF-kappaB promoter activity. In fact, p7 also prevented TNF-stimulated IkappaB degradation and even TRAF2 and TRAF6-driven NF-kappaB promoter activity, revealing the consistently strong immuno-modulatory effect of p7. In conclusion, here we have shown that p7 can modulate STAT3 and ERK signalling, leading to the upregulation of SOCS3 induction. This suggests a possible mechanism by which HCV could inhibit TNF signalling, thus limiting its inflammatory effects. This immuno-modulatory process may therefore explain why infection in many HCV patients remains silent. Overexpression of TNF has been implicated in the pathogenesis of several human inflammatory disorders, including Rheumatoid arthritis and Inflammatory bowel disease. Identification of HCV derived peptides that regulate TNF signalling may provide novel therapeutic avenues for their treatment.
APPROVED